Characterization of a Bend Sensor for Neuroprosthetic Applications - (:unkn) unknown (IEEE, 2017)
In this study, the static characterization of a bend sensor which is commonly used for various applications was performed. Electrical properties of the sensor was measured and analyzed on a robotic hand. Thus, the feasibility of the sensor for neuroprosthetic applications was discussed. The mean coefficient of determination (R-2) is 0.98 and the mean hysteresis value is 9.1 %. The joint angles on a robotic hand were estimated, but the results were different from the actual values because of the sensor placement method.